Patterns, risk factors and outcome predictors of posterior reversible encephalopathy syndrome in pediatric cancer patients. Issue 2 (28th January 2021) - Hafez, Hanafy A.; Ragab, Iman; Sedky, Mohamed; Shams, Marwa; Youssef, Ayda; Refaat, Amal; Habib, Elsaeed; Sidhom, Iman
Abstract: The purpose of this study was to assess the clinical and radiological patterns and outcome predictors of posterior reversible encephalopathy syndrome (PRES) in pediatric cancer patients. A retrospective study included patients who developed PRES during their treatment at the Children's Cancer Hospital Egypt. A total of 50 patients developed PRES. Leukemia and lymphoma were the commonest diagnoses (64%). Regarding the MRI findings, occipital affection was the most common (92%), followed by frontal and temporal lobes involvement in 32% and 22% respectively and advanced PRES was described in 8 patients. Of the whole patients, 80% had complete clinical resolution and 60% showed complete radiological resolution at 2 weeks' evaluation and 2 patients died out of PRES. Unfavorable outcome was associated with those who had motor dysfunction, status epilepticus at presentation, frontal lobe and thalamic affection and atypical PRES. PRES might present in atypical sites with poor outcome including death.